دراسة التباينات المورفولوجية والصفات الاقتصادية لعشائر الجزر المحلية Daucus carota L. (مجلة جامعة اللاذقية- سلسلة العلوم البيولوجية, 2018)
أجري البحث في مركز البحوث العلمية الزراعية باللاذقية بهدف دراسة صفات عشائر الجزر المحلية وخصائصها المورفولوجية والاقتصادية, وتحديد الطرز الوراثية التي تتمتع بصفات اقتصادية لاستخدامها في برامج التربية. استخدم في الدراسة عشر عشائر من الجزر المحلي. قسمت استناداً إلى لون الجذور إلى ثلاث مجموعات؛ المجموعة الأولى ضمت ست عشائر جذورها برتقالية اللون، والثانية ضمت ثلاث عشائر جذورها أرجوانية اللون، والثالثة احتوت عشيرة واحدة جذورها صفراء اللون. أظهرت النتائج تفوق العشيرة الثالثة من المجموعة الأولى, العشيرة الثالثة من المجموعة الثانية وعشيرة المجموعة الثالثة على بقية العشائر المدروسة إذ تميزت هذه العشائر بدليل حصاد مرتفع تراوح من ( 46 % ) إلى ( 63.9 % ), وبنسبة خشب إلى لحاء تراوحت من ( 65.2 % ) إلى ( 81.5 % ). كما أظهرت النتائج وجود علاقة ارتباطية بين حجم المجموعة الورقية وكل من دليل الحصاد, وزن الجذر ونسبة الخشب إلى اللحاء. This research has been conducted at the Agriculture Scientific Research Center in Lattakia. It studies the characters of local carrot populations and their morphological and economical traits in order to determine the best genotypes which have desirable economic traits to be used in breeding programs. It has been used ten populations which were divided according to root color into three groups: the first group included six populations which have orange roots, and the second group included three populations which characterized with their purple roots; while, the third one consisted of only one population with yellow roots. The results showed the following: 1 – The superiority of the 3rd population ( first group ), 3rd population ( second group) and the population of the 3rd group over the rest of the studied populations. 2 – The superiority of those populations can be attributed to their harvest index which ranged between 46 to 63.9 %, and to phloem / xylem ratio which ranged between 65.2 to 81.5 %. 3 – A relationship is present between canopy and each of harvest index, root weight and phloem / xylem ratio.